Pengaruh Kemampuan Bahasa, Literatur, dan Sumber Daya Akademik Digital dalam Efektivitas Administrasi - Ananto Krisna Wardhana; Riris Lestiowati; Kurniawan Utomo; Rachmat Fadly (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
This study aims to analyze human resource management in the context of academic digitalization through the variable of global language and literature. The research employs a descriptive mixed-method approach, combining both qualitative and quantitative techniques. Quantitative data are analyzed using AMOS version 28, while qualitative data are obtained through basic and advanced analysis techniques by examining various easily accessible digital literature sources such as the Digital Public Library of America (DPLA), Europeana Digital Library, HathiTrust Digital Library, Internet Archive, and Project MUSE. In addition, the study utilizes several online applications, including Google, Dropbox, Zoom, Skype, Microsoft Teams, and Slack, as well as language learning platforms such as Duolingo and Babbel. The exploration of academic publication digitalization is also conducted through the Directory of Open Access Journals (DOAJ) and other open-access portals. The findings indicate that digitalization has transformed the ways in which global language and literature are produced and utilized within academic settings. There is a positive and significant relationship between global language and literature and digital management in academia. Consequently, universities and schools have become more efficient in managing digital resources. However, the study also highlights concerns that technological advancement may reduce social interaction and diminish appreciation for cultural and literary values, particularly in the field of global language and literature. Keywords: Human resource management, digitalization, academics, language, global literature